Motivos de adherencia en los clubes deportivos del municipio de la Tebaida (Quindío) (2015)
This study called Grounds for adhesion sports town of La Tebaida (Quindio), has the general objective discern the motives of adhesion sports Quindio The Thebaid, in the course of this search, observations and depth interviews were applied, directly related to different factors binding or attachment to the sport as necessary tools for a better view of the target; the concurrence of the present inquiry, took into account a qualitative approach quasi-ethnographic, which enabled the end of the research project. Following the order of ideas, the population which was addressed were young people from the various sports clubs (skating, swimming, football) that have been highlighting in the town of La Tebaida Q. characteristics that these individuals had to have, is focused on an age range of between 14 and 28 years old and greater than or equal to six months in sport, to be observed, there was a random choice to be interviewed in depth continuity, in this interview part 4 men and 2 women, where it was possible to describe and interpret several possibilities of grip as the support of family, friends, coaches and others, which are categorized for deepening the analysis of these results.